Cell‐Free DNA in Metastatic Colorectal Cancer: A Systematic Review and Meta‐Analysis. (4th August 2017) - Spindler, Karen‐Lise G.; Boysen, Anders K.; Pallisgård, Niels; Johansen, Julia S.; Tabernero, Josep; Sørensen, Morten M.; Jensen, Benny V.; Hansen, Torben F.; Sefrioui, David; Andersen, Rikke F.; Brandslund, Ivan; Jakobsen, Anders
Abstract : Background: Circulating DNA can be detected and quantified in the blood of cancer patients and used for detection of tumor‐specific genetic alterations. The clinical utility has been intensively investigated for the past 10 years. The majority of reports focus on analyzing the clinical potential of tumor‐specific mutations, whereas the use of total cell‐free DNA (cfDNA) quantification is somehow controversial and sparsely described in the literature, but holds important clinical information in itself. The purpose of the present report was to present a systematic review and meta‐analysis of the prognostic value of total cfDNA in patients with metastatic colorectal cancer (mCRC) treated with chemotherapy. In addition, we report on the overall performance of cfDNA as source for KRAS mutation detection. Materials and Methods : A systematic literature search of PubMed and Embase was performed by two independent investigators. Eligibility criteria were (a) total cfDNA analysis, (b) mCRC, and (c) prognostic value during palliative treatment. The preferred reporting items for systematic reviews and meta‐analyses (PRISMA) guidelines were followed, and meta‐analysis applied on both aggregate data extraction and individual patients' data. Results : Ten eligible cohorts were identified, including a total of 1, 076 patients. Seven studies used quantitative polymerase chain reaction methods, two BEAMing [beads, emulsification, amplification, and magnetics] technology, and one study digital droplet polymerase chain reaction. The baseline levels of cfDNA was similar in the presented studies, and all studies reported a clear prognostic value in favor of patients with lowest levels of baseline cfDNA. A meta‐analysis revealed a combined estimate of favorable overall survival hazard ratio (HR) in patients with levels below the median cfDNA (HR = 2.39, 95% confidence interval 2.03–2.82, p  < .0001). Conclusion: The total cfDNA levels are high in patients with mCRC and bear strong prognostic information, which should be tested prospectively by using a predefined cut‐off value based on normal values in healthy cohorts. Finally, the potential use of cfDNA for detection of tumor‐specific mutations was emphasized in a large individual patients' data meta‐analysis. Abstract : Recently refined methods for cfDNA quantification and detection of mutations have been developed. Results of clinical investigations of the predictive and prognostic value of total cfDNA and plasma mutations in mCRC suggest a strong prognostic value of baseline plasma levels of cfDNA in this setting. This article presents a systematic review and meta‐analysis of the prognostic value of total plasma cfDNA in patients with mCRC treated with chemotherapy and/or targeted agents.